Fundamentals of chemistry - Goldberg, David E. (McGraw-Hill, 2001)
Designed for the one-semester preparatory chemistry course, the new, third edition of Fundamentals of Chemistry provides students with a solid foundation in problem solving for all the topic areas covered in a standard general chemistry course.. .